Grammar and Subject Content Ranking According to Language Levels in Teaching Turkish as a Second Language - Khozrevanidze, Mamuka; Arslan, Mustafa (Journal of Research in Turkic Languages, 2024)
The sequencing of grammar and content in the instruction of Turkish as a second language is crucial. Determining which topics and grammar rules will be taught at each level poses a challenge. The studies conducted so far on the subject have been carried out both institutionally and individually. Although some studies have been conducted in accordance with the levels specified in the Common European Framework of Reference for Languages, Turkish should be considered separately from European languages due to its belonging to a different language family and structure. In this study, the case study model was used within the scope of qualitative research. The data were obtained through observation and document analysis and interpreted through content analysis. In light of the findings obtained, the grammar and subject teaching sequence of Turkish as a second language has been shaped according to appropriate levels. While creating this sequence, emphasis was placed on the logical relationship between language grammar content and topics. 25 (13 DBİ, 12 Kİ), A2’de 23 (9 DBİ, 14 Kİ), B1’de 18 (10 DBİ, 8 Kİ), B2’de 24 ( 19 DBİ, 5 Kİ), C1’de 22 (16 DBİ, 6 Kİ) ve C2’de (7 DBİ, 3 Kİ) it was observed that grammar and subject content headings stand out in teaching Turkish as a foreign language. İkinci dil olarak Türkçenin öğretiminde dilbilgisi ve konu içeriğinin öğretim sıralaması çok önemlidir. Hangi seviyede hangi konu ve dilbilgisi kurallarının öğretileceği bir problem olarak ortaya çıkmaktadır. Konuyla ilgili bu zamana kadarki yapılan çalışmalar kurum ve şahıs bazında yapılan çalışmalardır. Diller İçin Avrupa Ortak Başvuru Metni’nde belirtilen seviyelere uygun olarak bazı çalışmalar yapılmış olsa da Türkçenin ait olduğu dil ailesi ve yapısı bakımından Avrupa dillerinden ayrı olarak düşünülmelidir. Bu çalışmada nitel araştırma kapsamında durum incelemesi modeli kullanılmıştır. Veriler gözlem ve doküman analizi yoluyla elde edilmiş ve içerik analizi ile yorumlanmıştır. Elde edilen bulgular ışığında ikinci dil olarak Türkçenin gramer ve konu öğretimi sıralaması seviyelere uygun olarak şekillendirilmiştir. Bu sıralama oluşturulurken dil biligisi içeriği ve konular arasındaki mantıksal ilişki üzerinde durulmuştur. A1’de 25 (13 DBİ, 12 Kİ), A2’de 23 (9 DBİ, 14 Kİ), B1’de 18 (10 DBİ, 8 Kİ), B2’de 24 ( 19 DBİ, 5 Kİ), C1’de 22 (16 DBİ, 6 Kİ) ve C2’de (7 DBİ, 3 Kİ) dilbilgisi ve konu içeriği başlığının yabancı dil olarak Türkçe öğretiminde öne çıktığı tespit edilmiştir.